Sams Teach Yourself Visual Studio® .NET 2003 in 21 Days - Beres, Jason (Sams Publishing, 2011)
Sams Teach Yourself Visual Studio .NET in 21 Days will help developers that are new to application development and experienced developers understand how to use the .NET Framework and Visual Studio .NET to rapidly develop any type of computer application. The Visual Studio .NET development environment is the most comprehensive developer tool ever created, putting that together with the .NET Frameworks' Class Libraries, the developer has everything he or she needs to get up-to-speed on Microsoft's latest revolution in application development. This book will guide the developer through using the VS .NET IDE, the Visual Basic .NET and C# language, and the supporting tools available from Microsoft to create Windows and Web-based applications. The market is full of books that pretty much say the same thing, which is already available in the help files, the author of this book has written and deployed over a dozen successful applications using Visual Studio .NET and the .NET Framework. All of his expertise and experience is used to give you the most comprehensive title on using Visual Studio .NET.